Multiple assays in a real-time RT-PCR SARS-CoV-2 panel can mitigate the risk of loss of sensitivity by new genomic variants during the COVID-19 outbreak. (August 2020) - Peñarrubia, Luis; Ruiz, Maria; Porco, Roberto; Rao, Sonia N.; Juanola-Falgarona, Martí; Manissero, Davide; López-Fontanals, Marta; Pareja, Josep
Highlights: Publicly available RT-PCR Panels detect SARS-CoV-2 targeting more than one genomic region. Genetic variability observed until week 21 is predicted to have no effect on panel sensitivity. The QIAstat-Dx SARS-CoV-2 Panel remains highly sensitive despite the nucleotide variations. Combination of multiple assays in RT-PCR SARS-CoV-2 panels mitigate possible sensitivity loss. Genetic variability assessment is critical to monitor sensitivity and specificity of the assays. Abstract: Objectives: In this study, five SARS-CoV-2 PCR assay panels were evaluated against the accumulated genetic variability of the virus to assess the effect on sensitivity of the individual assays. Design or methods: As of week 21, 2020, the complete set of available SARS-CoV-2 genomes from GISAID and GenBank databases were used in this study. SARS-CoV-2 primer sequences from publicly available panels (WHO, CDC, NMDC, and HKU) and QIAstat-Dx were included in the alignment, and accumulated genetic variability affecting any oligonucleotide annealing was annotated. Results: A total of 11, 627 (34.38%) genomes included single mutations affecting annealing of any PCR assay. Variations in 8, 773 (25.94%) genomes were considered as high risk, whereas additional 2, 854 (8.43%) genomes presented low frequent single mutations and were predicted to yield no impact on sensitivity. In case of the QIAstat-Dx SARS-CoV-2 Panel, 99.11% of the genomes matched with a 100% coverage all oligonucleotides, and critical variations were tested in vitro corroborating no loss of sensitivity. Conclusions: This analysis stresses the importance of targeting more than one region in the viral genome for SARS-CoV-2 detection to mitigate the risk of loss of sensitivity due to the unknown mutation rate during this SARS-CoV-2 outbreak.